Five Year Plan Progress Report for 1951-52 and 1952-53 - Planning Commission (Planning Commission, 1953)
In presenting the progress report on the working of the Five Year Plan during 1951-52 and 1952-53, a few words by way of introduction will perhaps be useful. the Plan was published as a draft in July, 1951. Many of the more important schemes included in the Plan were then in operation and commitments which had already been accepted by the Central and State Governments played a considerable part in shaping the Plan. During the eighteen months which separated the publication of the Draft Outline and the presentation of the final report on the Plan, there were important changes both in emphasis and in direction in several aspects.
Government of India Planning Commission